Unveiling the Enigma: Idiopathic Digital Infarction—A Case Report and Literature Review - Jaber H. Jaradat; Wadi Walid I; Aram F. Obeidat; Raghad Amro; Abdulqadir J. Nashwan (Clinical Case Reports, 2025)
ABSTRACT Idiopathic digital infarction (IDI), a rare subset of digital infarction, is characterized by ischemic changes in the absence of identifiable underlying etiology. We present the first documented case of IDI in a 47‐year‐old female with insignificant medical history. Clinical evaluation revealed bluish discoloration of the left lateral three fingers. Negative findings on autoimmune serologies, echocardiogram, and coagulation profiles excluded common causes, such as vasculitis, cardiac embolism, and hypercoagulable states. Imaging studies demonstrated ischemic changes in the left cerebellar hemisphere and proximal left subclavian artery, which supported the diagnosis of acute infarction. The patient was managed conservatively and was discharged. This case underscores the diagnostic complexities of IDI and highlights the importance of thorough evaluation and management.